2020
DOI: 10.1002/slct.202000659
|View full text |Cite
|
Sign up to set email alerts
|

An Azo Dye Based D‐π‐A Chromogenic Probe for Selective Naked‐Eye Detection of Hg2+ Ion: Application in Logic Gate Operation

Abstract: The current work describes the selective colorimetric detection of metal ions using a simple azo dye (L1) containing donor-πacceptor framework. In this chromogenic probe, salicylaldehyde is used as donor and nitrobenzene group as acceptor unit. L1 is found to show selective recognition of mercuric ion both visually and spectrophotometrically with no interference from environmentally relevant metal ions in DMSO-water mixture. It exhibits reddish-pink colour in DMSO-water medium as a result of intramolecular cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…The chromophoric moiety on the receptor R1 exhibits a strong push−pull π electron system with the nitro group as the acceptor and phenolic oxygen atom as the donor at the end of the azo benzene network. 29 Therefore, the chromophore displays strong intramolecular charge transfer phenomena (ICT) with eminent color due to extensive π electron conjugation. However, the ICT band disappeared after the addition of the Co 2+ metal ion.…”
Section: Investigation Of the Photophysical Properties Of Receptor R1...mentioning
confidence: 99%
“…The chromophoric moiety on the receptor R1 exhibits a strong push−pull π electron system with the nitro group as the acceptor and phenolic oxygen atom as the donor at the end of the azo benzene network. 29 Therefore, the chromophore displays strong intramolecular charge transfer phenomena (ICT) with eminent color due to extensive π electron conjugation. However, the ICT band disappeared after the addition of the Co 2+ metal ion.…”
Section: Investigation Of the Photophysical Properties Of Receptor R1...mentioning
confidence: 99%
“…The complex formation between sensor 89 and Hg 2+ restricted the ICT that caused blue-shift in absorbance, and the solution become colorless. Sensor 89 formed complex with Hg 2+ in 1:1 stoichiometric through the salicylaldehyde unit and the complexation reversed with the addition of F - [ 114 ].…”
Section: Chromo-fluorogenic Chemosensorsmentioning
confidence: 99%
“…In order to detect hazardous agents, azo molecules had outstanding chromogenic and fluorogenic behaviour toward a variety of cations (Cu + 2 , Fe + 2, and Hg + 2 ), anions (CN À , AcO À ), nitric oxide (NO) and picric acid (TNP), etc. [25][26][27][28][29][30][31] In continuation of our research endeavors and the literature, a survey revealed that less work has been done in the synthesis and in exploring the biological potentialities of mono-azo sulfonamide molecules. Keeping the above facts in mind, we have synthesized a series of sulfonamide mono-azo (À N=NÀ ) bonded molecules (T 1 -T 4 ), by reacting sulfamethizole with various coupling components such as-diphenylamine (DPA), N, N-dimethylaniline (DMA), 3-diethylaminophenol (3DEAP) and 2hydroxy-1,4-naphthoquinone (2H14NQ) under the suitable experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The environment and human health are harmed by some ions produced by industries and chemical warfare weapons like sarin, soman, and tabun that come from degradation products (hydrolysis). In order to detect hazardous agents, azo molecules had outstanding chromogenic and fluorogenic behaviour toward a variety of cations (Cu +2 , Fe +2, and Hg +2 ), anions (CN − , AcO − ), nitric oxide (NO) and picric acid (TNP), etc [25–31] …”
Section: Introductionmentioning
confidence: 99%